Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Sol Gel Dengan Variasi Rasio Ca/P Dan Waktu Aging - Zarkasi, Shoumi; A, Yelmida; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite is a bioceramics that is widely used as bone and dental grafting material, catalysts and adsorbents. Hydroxyapatite is a calcium phosphate compound that can be synthesized from natural ingredients with calcium content such as coral reefs. Coral reefs have a CaCO3 content of 94.6%. This study aims to synthesize hydroxyapatite through the formation of Precipitated Calcium Carbonate (PCC) from coral reefs. The research procedure begins with the coral calcination process to form CaO which is then used as PCC by carbonation method. PCC as a source of calcium was synthesized into hydroxyapatite using sol gel process with variations in Ca / P ratio (1.67; 1.77) and aging time (20; 24; 28; 32; 36 hours). Synthesized hydroxyapatite was analyzed by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDX) and Brunaur, Emmett and Teller (BET). FTIR analysis results showed that in each sample there were PO43- and OH groups which indicated calcium phosphate compounds had formed. XRD analysis results showed the formation of hydroxyapatite compounds from an angle of 2θ which corresponds to the data (ICDD 01-073-6113). Hydroxyapatite synthesized in the ratio of Ca / P 1.77 and aging time of 20 hours gave the best results with hexagonal crystal structure, crystal size of 10.08 nm, surface area of 90.413 m2 / g and mole ratio of Ca / P 1.71.Keywords : aging, carbonation, PCC, sol-gel method.